Upaya Dinas Perkebunan Dan Peternakan Kab. Aceh Barat Dalam Meningkatkan Kinerja Pegawai - Lana Fatisyah; Cut Nina Rostina (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
Performance evaluation plays an important role in knowing the activities of employees in a company that aims to achieve the vision and mission. Planners in an organization will be carried out if employees do a good job, in accordance with what has been determined. As employees, they must realize their performance by providing services to people who need help because the main task of government employees is to serve the community. Employees working in government should help the public if they need information about their business. The concept of the study of performance theory using evaluation theory by Hasibuan. The indicators contained therein are Achievement, Discipline, Creativity, Cooperation, and Responsibility. Employees must understand performance evaluation to help farmers. Informants are employees and the Department of Personnel. Researchers used the snowball sampling technique to obtain information. The method used by researchers in analyzing the data is a qualitative method with the Triangulation Technique. It aims to obtain data on employee performance evaluations at the Plantation and Livestock Service Office of West Aceh district in carrying out activities.